Endodontic treatment considerations in patients with special healthcare needs - Alsharif, Ainaa Abdulmoeen; Almuqhim, Osama Abdulmohsen; Alhowimel, Sliman Mohamad; Alfarran, Alanoud Sameer; Alotaibi, Rakan Nejer; Alhuwayji, Zahra Ahmed; Al-Bakri, Faisal Mohammed; Almotairi, Ibtisam Abdulaziz; Alhazmi, Lama Salman; Alanazi, May Awad; Alshumaymiri, Lama Abdullah (International Journal Of Community Medicine And Public Health, 2023)
Individuals with special needs may have conditions that are either present from birth, arise from environmental factors, or are acquired later in life. These conditions can significantly restrict their ability to engage in everyday activities, such as self-care tasks and essential life activities. Special needs encompass a wide range of conditions, including physical, developmental, mental, sensory, behavioral, and emotional impairments. These individuals may face challenges in communication and cooperation during dental treatment. Various medical conditions, such as cardiovascular diseases, hypertension, diabetes, bleeding disorders, and pregnancy, also impact endodontic care. Management strategies include careful evaluation, the use of general anesthesia, and minimizing technical compromises. Dental professionals deal with individuals in their everyday routines who suffer from a variety of medical conditions and special circumstances The review further discusses considerations for patients with bleeding disorders, diabetes, lung disorders, HIV, and those undergoing cancer treatment. Finally, it highlights the unique challenges of providing endodontic care to elderly patients and COVID-19-positive individuals, emphasizing the importance of safety protocols during the pandemic.